Persepsi Siswa Tentang Full Day School Terhadap Hasil Belajar Geografi IPS Kelas XI SMA Negeri 5 Kabupaten Luwu - Anggraini, Ningsi (UNIVERSITAS NEGERI MAKASSAR, 2019)
This study aims to find out: 1) Application of students about full day school; 2) student learning outcomes; 3) students' application of full day school to learning outcomes. This research is an ex post facto research. The independent variable is the application of students about full day school and the dependent variable is student learning outcomes. The population of class XI IPS students amounted to 86 students, the sample was taken 100%, namely 86 students. Data collection through observation, questionnaires, and documentation of students' final grades. Data analysis used descriptive and inferential analysis of Product Moment correlation, simple liner regression and multivariate analysis. The results of the study show that: 1) the application of full day school has a percentage of 42.36%, which is quite good; 2) student learning outcomes have a percentage of 47.67% including very good categories; 3) the results of the multivariate analysis showed that the full school variable had a significant effect on learning outcomes with a significant 0.00 <0.05. This meant that Ha was accepted and Ho was rejected. This means that the better the implementation of full school, the better the student learning outcomes and vice versa. This can be shown by the equation Y = 35.840 + 0.601X with a correlation coefficient of 0.883 and a coefficient of determination of 0.78. This figure shows that the fullday school system affects 78% of students' geography learning outcomes, while the remaining 22% is affected by other factors not examined in this study.